Information and direction to such persons as are inclined to America, more especially those related to the Province of Pensilvania - Penn, William, 1644-1718 ([publisher not identified], 1686)
1686 Reprint of William Penn's pamphlet on Information and Direction to such Persons as are Inclined to America, more especially those related to the Province of Pennsylvania. This document served as an immigrant guide regarding costs, land, weather and other pertinent information.